Polyamideimide copolymer and film using the same
Patent Information
- Application Number
- KR1020237003576
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-30
- Filing Date
- 2021-09-29
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2041-09-29
Smart Images

Figure 112023011291823-PCT00018_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a polyamideimide copolymer suitable for use in a cover window of a foldable display element, such as a foldable device. Background Technology
[0002] Foldable devices have recently been attracting attention in order to further enhance the portability of portable information terminals such as smartphones and tablets. For components such as cover windows used in the flexible displays that constitute these foldable devices, it was necessary to possess flexibility in addition to transparency. Specifically, there is a demand for components with very high flexibility that can achieve a 180° bend with a small bending radius of about 2.5 mm.
[0003] In contrast, various materials containing flexible organic polymers are being considered as alternatives to conventional rigid glass. For example, films containing polyimide resin as a flexible organic polymer have been investigated and proposed in terms of transparency and heat resistance.
[0004] However, in flexible displays using films containing organic polymers with such flexibility, pressure marks or bending marks sometimes occurred on the display surface when operated by tactile feedback or a stylus, or when the display was maintained in a folded state for a long time. Therefore, for such flexible displays, it became necessary to possess a high elastic modulus in addition to high flexibility. In response to this challenge, conventional fluorine-substituted polyimide films have attracted attention as films for flexible displays that combine heat resistance, transparency, mechanical strength, surface hardness, and bending resistance.
[0005] However, in the field of recent foldable devices, along with further improvements in functionality and productivity and diversification of design and applications, polyimide copolymers that maintain transparency while further improving solubility in solvents and bending resistance during processing, and polyamideimide copolymers that further improve mechanical strength have been proposed as cover window films for foldable devices (Patent Document 1 et al.). Prior art literature
[0006] Japanese Patent Publication No. 2014-528490 The problem to be solved
[0007] The polyamideimide copolymer proposed in the above patent document 1, etc., has an imide structural unit that uses a fluorine-substituted acid anhydride such as 4,4'-(hexafluoroisopropylidene)diphthalic acid dianhydride (6FDA) as a tetracarboxylic acid dianhydride component contributing to solubility or transparency, an acid anhydride such as 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (sBPDA) as a tetracarboxylic acid dianhydride component contributing to bending resistance, and an amide structural unit that uses terephthalic acid chloride (TPC) as a dicarboxylic acid component contributing to mechanical strength.
[0008] However, in copolymers using fluorine-substituted acid anhydrides such as 6FDA, the surface wettability and adhesion are poor when made into a film, so surface treatment is required when laminating the film with other substrates or coating materials.
[0009] In addition, although the toughness, such as the flexural strength of the copolymer, is improved by using acid anhydrides with intermolecular interactions like sBPDA, the YI value (yellowness) of the copolymer tends to increase due to π-electron conjugation, and it was necessary to add a blueing agent to the film to reduce the YI value. Consequently, in applications where colorless transparency is required, such as cover window films, the light transmittance was insufficient.
[0010] Accordingly, the objective of the present invention is to provide a polyamideimide copolymer that has excellent toughness, such as flexural strength, as well as excellent transparency, and also has good wettability and adhesion when made into a film. means of solving the problem
[0011] The inventors, focusing on the imide structural unit of a polyamideimide copolymer, investigated various tetracarboxylic acid dianhydrides and obtained knowledge that the above problem can be solved by combining two specific tetracarboxylic acid dianhydrides. The present invention was completed based on this knowledge. The gist of the present invention is as follows.
[0012] [1] A polyamideimide copolymer comprising imide structural units and amide structural units,
[0013] The above imide structural unit is an imide structural unit I-1, which is expressed by the following formula (1):
[0014]
[0015] and
[0016] At least one imide structural unit I-2 selected from the group consisting of those represented by the following formulas (2) to (5):
[0017]
[0018] (In formulas (1) to (5), X1 to X5 each independently represent a divalent organic group derived from a diamine.)
[0019] Includes,
[0020] The above amide structural unit is an amide structural unit A represented by the following formula (6):
[0021]
[0022] (In the formula, X6 represents a divalent organic group derived from a diamine, and Y represents a divalent organic group derived from a dicarboxylic acid or a dicarboxylic acid derivative.)
[0023] A polyamideimide copolymer characterized by including
[0024] [2] X1 to X6, the following formula (7):
[0025]
[0026] (In the formula, * is a combiner.)
[0027] The polyamideimide copolymer described in [1], represented as.
[0028] [3] Y, the following formulas (8) to (10):
[0029]
[0030] (In the formula, * is a combiner.)
[0031] A polyamideimide copolymer described in [1] or [2], at least one selected from [1].
[0032] [4] A polyamideimide copolymer described in any one of [1] to [3], wherein the above imide structural unit I-2 is represented by the above formula (2).
[0033] [5] A polyamideimide copolymer described in any one of [1] to [4], wherein the above imide structural unit and the above amide structural unit are included in a molar ratio of 2:8 to 8:2.
[0034] [6] A film comprising a polyamideimide copolymer as described in any of [1] to [5].
[0035] [7] A film described in [6] having a water contact angle of 55 degrees or less on the surface of a film with a thickness of 50 μm as measured in accordance with JIS R3257:1999.
[0036] [8] A film described in [6] or [7] used as a cover window for a foldable device. Effects of the invention
[0037] According to the present invention, by using an imide structural unit that combines two specific tetracarboxylic acid dianhydrides, it is possible to realize a polyamideimide copolymer that has excellent toughness such as flexural resistance, excellent transparency, and also good wettability and adhesion when made into a film. Specific details for implementing the invention
[0038] [Polyamideimide copolymer]
[0039] The polyamideimide copolymer according to the present invention is a copolymer having an imide structure and an amide structure, and as an imide structural unit, it has at least one imide structural unit I-2 selected from the group consisting of an imide structural unit I-1 represented by the following formula (1) and one represented by the following formulas (2) to (5), and as an amide structural unit, it has an amide structural unit A represented by the following formula (6).
[0040]
[0041]
[0042]
[0043] In the present invention, as an imide structural unit constituting the polyamideimide copolymer, by combining structural unit I-1 represented by formula (1) and one or more structural units I-2 of (2) to (5), the transparency of the polyamideimide copolymer and the wettability and adhesion to other materials when made into a film can be simultaneously improved. As with conventional polyamideimide copolymers, if a fluorine-substituted tetracarboxylic acid dianhydride such as 6FDA is used as the tetracarboxylic acid dianhydride component of the imide structural unit, the transparency of the polyamideimide copolymer obtained is improved, but the wettability and adhesion when made into a film are insufficient. In the present invention, as a result of screening various tetracarboxylic acid dianhydrides in terms of electron affinity, at least one selected from the group consisting of 3,4-oxydiphthalic acid dianhydride (aODPA), 4,4'-oxydiphthalic acid dianhydride (sODPA), 2,2',3,3'-biphenyltetracarboxylic acid dianhydride (aBPDA), 9,9-bis(3,4-dicarboxyphenyl)fluorene acid anhydride (BPAF), and 4,4'-(hexafluoroisopropylidene)diphthalic acid dianhydride (6FDA) is combined, thereby simultaneously improving the transparency of the resin and the wettability and adhesion when made into a film compared to a conventional polyamideimide copolymer combining 6FDA and sBPDA, without damaging various properties derived from the imide structure such as heat resistance or mechanical strength.
[0044] Among structural unit I-2 of (2) to (5) combined with structural unit I-1 expressed by the above formula (1), the structural unit expressed by the above formula (2) is preferred. That is, in the present invention, a combination of aODPA and sODPA is preferred as the tetracarboxylic acid dianhydride constituting the imide structural unit.
[0045] The ratio of I-1 and I-2 constituting the imide structural units of the polyamideimide copolymer is preferably in the range of 2:1 to 1:2 in molar ratio, and more preferably in the range of 3:2 to 2:3.
[0046] In the polyamideimide copolymer of the present invention, as an imide structural unit, components other than those described above may be included within a range that does not impair the effects of the present invention. As tetracarboxylic acid components constituting the imide structural unit, various tetracarboxylic acids or tetracarboxylic acid derivatives are available, and tetracarboxylic acid derivatives may include anhydrides of tetracarboxylic acids, preferably dianhydrides, acid chlorides, etc. As tetracarboxylic acid compounds, examples include aromatic tetracarboxylic acid compounds such as aromatic tetracarboxylic acids and their anhydrides, preferably their dianhydrides; aliphatic tetracarboxylic acid compounds such as aliphatic tetracarboxylic acid compounds and their anhydrides, preferably their dianhydrides, etc. These tetracarboxylic acid compounds may be used alone or in combination of two or more types.
[0047] Specific examples of aromatic tetracarboxylic acid dianhydrides include non-condensing polycyclic aromatic tetracarboxylic acid dianhydrides, monocyclic aromatic tetracarboxylic acid dianhydrides, and condensing polycyclic aromatic tetracarboxylic acid dianhydrides. As non-condensing polycyclic aromatic tetracarboxylic acid dianhydrides, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (sBPDA), 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic acid dianhydride (BPADA), 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride, 2,2',3,3'-benzophenonetetracarboxylic acid dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic acid dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 2,2-bis(3,4-dicarboxyphenoxyphenyl)propane dianhydride, Examples include 1,2-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,2-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, 4,4'-(p-phenylenedioxy)diphthalic acid dianhydride and 4,4'-(m-phenylenedioxy)diphthalic acid dianhydride. In addition, examples of monocyclic aromatic tetracarboxylic acid dianhydrides include 1,2,4,5-benzenetetracarboxylic acid dianhydrides, and examples of condensed polycyclic aromatic tetracarboxylic acid dianhydrides include 2,3,6,7-naphthalenetetracarboxylic acid dianhydrides.
[0048] Examples of aliphatic tetracarboxylic acid dianhydrides include cyclic or non-cyclic aliphatic tetracarboxylic acid dianhydrides. Cyclic aliphatic tetracarboxylic acid dianhydrides are tetracarboxylic acid dianhydrides having an alicyclic hydrocarbon structure, and specific examples thereof include cycloalkanetatecarboxylic acid dianhydrides such as 1,2,4,5-cyclohexanetetracarboxylic acid dianhydride (HPMDA), 1,2,3,4-cyclobutanetetracarboxylic acid dianhydride (CBDA), and 1,2,3,4-cyclopentanetetracarboxylic acid dianhydride, bicyclo[2.2.2]oct-7-en-2,3,5,6-tetracarboxylic acid dianhydride, dicyclohexyl-3,3',4,4'-tetracarboxylic acid dianhydride (HBPDA), and positional isomers thereof. These may be used individually or in combination of two or more types. Specific examples of acyclic aliphatic tetracarboxylic acid dianhydrides include 1,2,3,4-butanetetracarboxylic acid dianhydride and 1,2,3,4-pentanetetracarboxylic acid dianhydride, and these may be used individually or in combination of two or more types. In addition, a cyclic aliphatic tetracarboxylic acid dianhydride and an acyclic aliphatic tetracarboxylic acid dianhydride may be used in combination.
[0049] The imide structural unit may include, in addition to the above structural unit, a water adduct of the tetracarboxylic acid dianhydride or a structural unit derived from a tricarboxylic acid compound, provided that the effect of the present invention is not impaired. Examples of tricarboxylic acid compounds include aromatic tricarboxylic acids, aliphatic tricarboxylic acids and their flexible acid chloride compounds, acid anhydrides, etc., and two or more may be used in combination. Specific examples include anhydride of 1,2,4-benzenetricarboxylic acid; 2,3,6-naphthalenttricarboxylic acid-2,3-anhydride; and compounds in which phthalic anhydride and benzoic acid are connected by a single bond, -O-, -CH2-, -C(CH3)2-, -SO2-, or phenylene group.
[0050] The polyamideimide copolymer according to the present invention comprises an amide structural unit A represented by the following formula (6). By making a copolymer having an imide structure with rigid properties and an amide structure with flexible properties, it is possible to realize mechanical properties at a high level that are in a trade-off relationship between excellent flexibility and high elasticity without sacrificing transparency or wettability.
[0051]
[0052] (In the formula, X6 represents a divalent organic group derived from a diamine, and Y represents a divalent organic group derived from a dicarboxylic acid or a dicarboxylic acid derivative.)
[0053] The polyamideimide copolymer containing the above-mentioned amide structural unit A is obtained by reacting monomer components such as a diamine compound, a tetracarboxylic acid compound, and a dicarboxylic acid compound. Specifically, a polymer having an imide precursor structure is synthesized by reacting a diamine compound with a tetracarboxylic acid compound, and then a copolymer having an imide precursor structure and an amide structure is synthesized by reacting the said polymer with a dicarboxylic acid compound, and then the imide precursor structure in the said copolymer is obtained by performing a ring-closing reaction (imidization).
[0054] The polyamideimide copolymer has a structure in which a residue formed by reacting a diamine compound with a tetracarboxylic acid compound is bonded through an imide structure to a constituent unit in which a residue formed by reacting a dicarboxylic acid compound is bonded through an amide structure.
[0055] In the amide structural unit A represented by the above formula (7), Y is a divalent organic group derived from a dicarboxylic acid or a dicarboxylic acid derivative, and examples of dicarboxylic acid derivatives include the acid chloride or ester of the said dicarboxylic acid. The dicarboxylic acid can be used alone or in combination of two or more types.
[0056] Specific examples of dicarboxylic acids include, for example, 1,3-cyclobutanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 4,4'-oxybisbenzoic acid, terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 4,4'-biphenyldicarboxylic acid, 3,3'-biphenyldicarboxylic acid, compounds in which two cyclohexanedicarboxylic acids or two benzoic acids are connected by a single bond, -CH2-, -C(CH3)2-, -C(CF3)2-, -SO2-, or phenylene groups, alicyclic dicarboxylic acids or aromatic dicarboxylic acids and their derivatives (e.g., acid chlorides, acid anhydrides); Examples include aliphatic dicarboxylic acids such as dicarboxylic acid compounds of chain hydrocarbons having 8 or fewer carbon atoms, and their derivatives (e.g., acid chlorides, esters). These dicarboxylic acid compounds may be used alone or in combination of two or more.
[0057] Among these, in order to improve the break point elongation or elastic modulus as a film, it is preferable to use terephthalic acid, isophthalic acid, 4,4'-biphenyldicarboxylic acid, or 4,4'-oxybisbenzoic acid or its derivatives, in particular terephthalic acid chloride (TPC), isophthalic acid chloride (IPC), 4,4'-biphenyldicarbonyl chloride (BPC), or 4,4'-oxybis(benzoyl chloride) (OBBC). Specifically, it is preferable to have an amide structural unit A-1 represented by the following formula (11), where Y is a divalent organic group derived from TPC; an amide structural unit A-2 represented by the following formula (12), where Y is a divalent organic group derived from IPC; or an amide structural unit A-3 represented by the following formula (13), where Y is a divalent organic group derived from BPC. It is particularly preferable to have an amide structural unit A-1.
[0058]
[0059] (In the formula, X6 represents a divalent organic group derived from a diamine.)
[0060] As an amide structural unit, the above-mentioned amide structural unit A-1 and other amide structural units may be used in combination. Examples of other amide structural units include those derived from the above-mentioned various dicarboxylic acids or dicarboxylic acid derivatives, but amide structural unit A-2 or A-3 is preferred. When amide structural unit A-1 and A-2 or A-3 are used in combination as amide structural units, the composition ratio is preferably in the range of 10:1 to 5:1 from the perspective of the balance between optical properties such as transparency and mechanical properties such as mechanical strength.
[0061] In the polyamideimide copolymer of the present invention, the composition ratio (molar ratio) of the imide structure and the amide structure is preferably 0.5 to 4:3 to 6.5, more preferably 1.5 to 3.5:3.5 to 5.5, and particularly preferably 3:4, and by having the composition ratio of the imide structure and the amide structure as described above, excellent flexibility and high elasticity can be achieved in good balance.
[0062] The diamine component constituting the above-mentioned imide structural unit and amide structural unit (i.e., a divalent organic group represented by X1 to X6) is not particularly limited, and any diamine component used in conventionally known polyimides or polyamideimides may be used, such as aliphatic diamines, aromatic diamines, and mixtures thereof.
[0063] In addition, "aromatic diamine" herein refers to a diamine in which an amino group is directly bonded to an aromatic ring, and may include an aliphatic group or other substituents in part of its structure. This aromatic ring may be a monocyclic ring or a condensed ring, and examples include, but are not limited to, benzene rings, naphthalene rings, anthracene rings, and fluorene rings. Among these, it is preferably a benzene ring. In addition, "aliphatic diamine" refers to a diamine in which an amino group is directly bonded to an aliphatic group, and may include an aromatic ring or other substituents in part of its structure. Diamine compounds may be used alone or in combination of two or more types.
[0064] Specific examples of aliphatic diamines include acyclic aliphatic diamines such as hexamethylenediamine; cyclic aliphatic diamines such as 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, norbornandiamine, and 4,4'-diaminodicyclohexylmethane. These can be used alone or in combination of two or more types.
[0065] Specific examples of aromatic diamines include aromatic diamines having one aromatic ring, such as p-phenylenediamine, m-phenylenediamine, 2,4-toluenediamine, m-xylylenediamine, p-xylylenediamine, 1,5-diaminonaphthalene, 2,6-diaminonaphthalene; 4,4'-Diaminodiphenylmethane, 4,4'-Diaminodiphenylpropane, 4,4'-Diaminodiphenyl ether, 3,4'-Diaminodiphenyl ether, 3,3'-Diaminodiphenyl ether, 4,4'-Diaminodiphenylsulfone, 3,4'-Diaminodiphenylsulfone, 3,3'-Diaminodiphenylsulfone, 1,4-Bis(4-aminophenoxy)benzene, 1,3-Bis(4-aminophenoxy)benzene, Bis[4-(4-aminophenoxy)phenyl]sulfone, Bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2-Bis[4-(4-aminophenoxy)phenyl]propane, 2,2-Bis[4-(3-aminophenoxy)phenyl]propane, 2,2'-Dimethylbenzidine, 2,2'-Bis(trifluoromethyl)benzidine, Examples of aromatic diamines having two or more aromatic rings include 4,4'-bis(4-aminophenoxy)biphenyl, 9,9-bis(4-aminophenyl)fluorene, 9,9-bis(4-amino-3-methylphenyl)fluorene, 9,9-bis(4-amino-3-chlorophenyl)fluorene, 9,9-bis(4-amino-3-fluorophenyl)fluorene, 4-aminophenyl-4'-aminobenzoate, (2-phenyl-4-aminophenyl)-4-aminobenzoate, 4,4'-diaminobenzanilide, etc. These can be used alone or in combination of two or more.
[0066] Among the above diamine compounds, in order to improve colorless transparency or elasticity as a film, it is preferable to use one or more selected from the group consisting of aromatic diamines having a biphenyl structure, specifically one or more selected from the group consisting of 2,2'-dimethylbenzidine, 2,2'-bis(trifluoromethyl)benzidine, 4,4'-bis(4-aminophenoxy)biphenyl, and 4,4'-diaminodiphenyl ether. Furthermore, in order to improve colorless transparency, it is more preferable to use a diamine having a biphenyl structure in which some or all of the aromatic cyclic hydrogen atoms are substituted with a substituent selected from a fluoro group, a trifluoromethyl group, or a trifluoromethoxy group, specifically 2,2'-bis(trifluoromethyl)benzidine (TFMB) expressed by the following formula.
[0067]
[0068] As a diamine compound, the above-mentioned TFMB may be used alone, or one or more of the above-mentioned various diamine compounds may be used in combination with TFMB. When TFMB and other various diamine compounds are used in combination, the composition ratio is preferably in the range of 10:1 to 5:1 from the perspective of the balance of optical properties such as transparency and mechanical properties such as mechanical strength.
[0069] In the synthesis of a polyamideimide copolymer, the composition ratio of monomer components (diamine compound:tetracarboxylic acid compound:dicarboxylic acid compound) is preferably 7:0.5 to 4:3 to 6.5 as a molar ratio, more preferably 7:1.5 to 3.5:3.5 to 5.5, and particularly preferably 7:3:4.
[0070] The ring-closing reaction (imidation) of the imide precursor obtained by reacting the above-mentioned diamine compound with a tetracarboxylic acid compound, or the imide precursor reacting the diamine compound, the tetracarboxylic acid compound, and the dicarboxylic acid compound, can be either thermal imidation, in which an azeotropic solvent that azeotropically combines with water (e.g., toluene, xylene, etc.) is added and heated, or chemical imidation, in which a condensation agent and a reaction promoter are used, but chemical imidation is preferred in that colorless transparency is maintained.
[0071] Examples of reaction promoters used for chemical imidation include triethylamine, diisopropylethylamine, N-methylpiperidine, pyridine, 2-methylpyridine, 3-methylpyridine, 4-methylpyridine, 3-ethylpyridine, 3,5-dimethylpyridine, 3,5-diethylpyridine, isoquinoline, imidazole, 1-methylimidazole, 2-methylimidazole, and 1,2-dimethylimidazole. These reaction promoters may be one type or a combination of two or more types.
[0072] Examples of condensation agents used for chemical imidation include acid anhydrides such as acetic anhydride, propionic anhydride, and trifluoroacetic anhydride, phosphite esters, triethyl phosphite, triethyl phosphite, tributyl phosphite, dimethyl phosphite, diethyl phosphite, and triphenyl phosphite. These condensation agents may be one type or a combination of two or more types.
[0073] The imidization rate is preferably 90% or more, more preferably 93% or more, and even more preferably 96% or more. From the perspective of facilitating the improvement of optical homogeneity, such as transparency, a higher imidization rate is preferable. Additionally, the upper limit of the imidization rate is 100% or less. The imidization rate represents the ratio of the molar amount of imide bonds in the imide structural unit to twice the molar amount of constituent units derived from tetracarboxylic acid dianhydrides in the imide structural unit. Furthermore, the imidization rate can be determined by the IR method, NMR method, etc.
[0074] The organic solvent used for the synthesis of polyamideimide copolymers is not particularly limited as long as it is an organic solvent that is inert to the reaction. Examples include N,N-dimethylacetamide (DMAc), N-methyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, dimethyl sulfoxide, m-cresol, γ-butyrolactone, cyclopentanone, cyclohexanone, tetrahydrofuran, etc. These organic solvents may be used individually or in combination of two or more types.
[0075] The reaction conditions for synthesis can be 1 to 27 hours or less at 10 to 50°C, and it is preferable to synthesize under a nitrogen atmosphere to maintain colorless transparency.
[0076] The polyamideimide copolymer may be isolated (separated and purified) by conventional separation means, such as filtration, concentration, extraction, crystallization, recrystallization, column chromatography, or a combination thereof. In a preferred embodiment, the copolymer may be isolated by adding a large amount of alcohol, such as methanol, to a reaction solution containing a transparent polyamideimide resin, precipitating the resin, and then performing concentration, filtration, drying, etc.
[0077] The weight average molecular weight (Mw) of the resin having an imide structure obtained as described above is preferably in the range of 50,000 to 1,000,000, more preferably in the range of 80,000 to 800,000, and even more preferably in the range of 110,000 to 650,000, from the perspective of improving elastic modulus or break point elongation. In addition, the weight average molecular weight (Mw) refers to a value calculated by polystyrene conversion after measuring by GPC (gel permeation chromatography).
[0078] Film
[0079] The polyamideimide copolymer of the present invention can be dissolved in a suitable solvent to form a resin composition (resin varnish), and the resin composition is applied onto a support to form a coating film. Then, the coating film is dried to remove the solvent, and the film is peeled off from the support to obtain a film. As for the solvent, any solvent capable of dissolving polyamideimide can be used without particular limitation. However, from the perspective of the applicability of the resin varnish and the transparency of the resulting film, a solvent comprising at least one selected from the group consisting of ester groups, ether groups, ketone groups, hydroxyl groups, sulfonate groups, and sulfinyl groups is preferred.
[0080] Examples of solvents having ester groups include ester-based solvents, such as methyl acetate, ethyl acetate, butyl acetate, and dimethyl carbonate.
[0081] Examples of solvents having a cyclic ester group include lactone-based solvents, such as γ-butyrolactone (GBL), δ-valerolactone, ε-caprolactone, γ-crotonolactone, γ-hexanolactone, α-methyl-γ-butyrolactone, γ-valerolactone, α-acetyl-γ-butyrolactone, δ-hexanolactone, etc.
[0082] Examples of solvents having an ether group include tetrahydrofuran, dioxane, and dibutyl ether.
[0083] Examples of solvents having a ketone group include ketone-based solvents, such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone.
[0084] Examples of solvents having hydroxyl groups include phenolic solvents, such as m-cresol.
[0085] Examples of solvents having a sulfonate group include methylsulfone, ethylphenylsulfone, diethylsulfone, diphenylsulfone, sulfolane, bisphenol S, solapson, dapsone, bisphenol A polysulfone, sulfolane, etc.
[0086] Examples of solvents having a sulfinyl group include sulfoxide-based solvents, such as N,N-dimethylsulfoxide (DMSO).
[0087] In addition to the solvents listed above, amide-based solvents, such as N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), etc., may be used.
[0088] The resin composition for making a film may include any component other than a polyamideimide copolymer, and examples include a leveling agent, dispersant, surfactant, retardation adjuster, antioxidant, UV inhibitor, light stabilizer, plasticizer, wax, filler, pigment, dye, foaming agent, defoaming agent, dehydrating agent, antistatic agent, antibacterial agent, antifungal agent, and a bluing agent for reducing the yellowness of the film.
[0089] The content of the polyamideimide copolymer in the resin composition is preferably in the range of 65 to 100 mass% with respect to the total amount of solids excluding the solvent, more preferably in the range of 80 to 100 mass%, and even more preferably in the range of 90 to 100 mass%.
[0090] As a means for applying a resin composition containing a polyamideimide copolymer onto a support, conventionally known means may be applied, such as dip coat method, flow coat method, roll coat method, bar coater method, blade coater method, screen printing method, curtain coat method, spray coat method, etc.
[0091] There are no particular restrictions on the drying conditions of the coating film as long as the temperature at which the solvent volatilizes, but from the perspective of obtaining a film with excellent transparency, it is preferable to dry it at 60 to 250°C for about 10 to 60 minutes.
[0092] The film of the present invention preferably has a film thickness of 5 μm or more and 100 μm or less, and more preferably 10 μm or more and 50 μm or less. By setting the film thickness to the above-described range, the film can be made into a film with excellent flexibility, so the film can be suitably used as a cover window for a foldable display or a flexible display. The film thickness can be adjusted by the amount of resin composition applied.
[0093] As the film of the present invention is formed from a polyamideimide copolymer containing two specific types of imide structural units as described above, it has excellent toughness such as flexural strength, excellent transparency, and also good surface wettability and adhesion to other materials. For example, in a single-layer film with a thickness of 50 μm formed from a polyamideimide copolymer, the YI value can be 2.0 or less. In addition, in this specification, the YI value (yellowness) refers to a value calculated based on the formula YI = 100 × (1 - 0.847 Z) / Y by measuring the transmittance of light of 360 to 780 nm using a spectrophotometer in accordance with ASTM E313-73 to obtain three stimulus values (X, Y, Z).
[0094] In addition, the film of the present invention has excellent wettability and adhesion, and for example, a film formed on a glass substrate with a film thickness of 50 μm and having an arithmetic mean surface roughness Ra of 50 nm or less has a water contact angle of 55 degrees or less. As such, since the film of the present invention has excellent wettability even when the surface is smooth, unlike conventional polyimideamide films, there is no need to perform surface treatment of the film when, for example, the film is bonded to another substrate or laminated with a coating film containing a decorative coloring material. In addition, the water contact angle refers to the water contact angle measured in accordance with JIS R3257:1999, and the arithmetic mean surface roughness Ra refers to the value measured by a measuring device in accordance with JIS B0601-1994.
[0095] [use]
[0096] Examples of display components using the film of the present invention include thin and bendable foldable type organic EL displays, portable terminals such as smartphones or wristwatches, display devices inside automobiles, and flexible panels used in wristwatches. Additionally, it may be applied to components for image display devices such as liquid crystal displays and organic EL displays, components for touch panels, flexible printed circuit boards, components for solar cell panels such as surface protective films or substrate materials, components for optical waveguides, and other semiconductor-related components. Among these, it is suitably used for components such as cover windows or TFT substrates that constitute a foldable type organic EL display.
[0097] [Display cover window]
[0098] As a cover window for a display using the film of the present invention, for example, the film is positioned on the surface of various displays. The method of positioning on the surface is not particularly limited, but, for example, a method involving an adhesive layer may be used. As the material of the adhesive layer, conventionally known adhesive materials that can be used for bonding surface materials for displays may be used. Furthermore, the cover window for a display using the film of the present invention may further provide a protective layer, such as a hard coat layer, or a fingerprint-preventing layer on the film surface.
[0099] [Substrate for TFTs in Organic EL Displays]
[0100] A substrate for a TFT of an organic EL display using the film of the present invention is obtained, for example, by forming an amorphous silicon TFT (thin-film transistor) on the film of the present invention. The TFT includes a gate metal layer, a silicon nitride gate dielectric layer, and an ITI pixel electrode. In addition, a structure required for an organic EL display may be formed on this by a known method, and the method of forming circuits, etc. is not particularly limited.
[0101] Examples
[0102] The present invention will be explained in more detail below through examples, but the present invention is not limited to these examples. Furthermore, "parts" and "%" in the following description are all based on mass unless otherwise specified.
[0103] [Example 1]
[0104] Preparation of Polyamideimide
[0105] 60.9 g of DMAc was charged into a 100 mL reactor, and 4.849 g (15.14 mmol) of TFMB was added. Subsequently, 1.007 g (3.245 mmol) of aODPA and 1.4875 g (3.245 mmol) of BPAF were added to this TFMB solution, and the mixture was reacted by stirring at 30°C for 2 hours to obtain a solution containing a polymer having an imide precursor structure. Then, 1.757 g (8.653 mmol) of TPC was added to this solution, and the mixture was reacted by stirring for 1.5 hours while maintaining the liquid temperature at 30°C to obtain a solution containing a copolymer having an imide precursor structure and an amide structure.
[0106] Subsequently, 2.09 g of pyridine, 2.45 g of acetic anhydride, and 8.53 g of DMAc were added and stirred at 20 to 30°C for 8 hours to obtain a polyamideimide solution. Additionally, 99 g of DMA was added and stirred until homogeneous. Then, this solution was gradually added to a container containing 4 L of methanol to precipitate the mixture. The precipitated solid was filtered and ground, and then dried under vacuum at 80°C for 8 hours to obtain a polyamideimide copolymer (PAI-1) with a solid powder of 8.2 g. The weight-average molecular weight of polystyrene equivalent by GPC was 597,000.
[0107] [Example 2]
[0108] A polyamideimide solution was obtained in the same manner as in Example 1, except that 0.9547 g (3.245 mmol) of aBPDA was added instead of BPAF. The obtained polyamideimide solution was purified in the same manner as in Example 1 to obtain a polyamideimide copolymer (PAI-2) with a solid content of 8.0 g. The weight average molecular weight of polystyrene equivalent by GPC was 201,000.
[0109] [Example 3]
[0110] A polyamideimide solution was obtained in the same manner as in Example 1, except that 1.007 g (3.245 mmol) of sODPA was added instead of BPAF. The obtained polyamideimide solution was purified in the same manner as in Example 1 to obtain a polyamideimide copolymer (PAI-3) with a solid content of 7.9 g. The weight-average molecular weight of polystyrene equivalent by GPC was 407,000.
[0111] [Example 4]
[0112] A polyamideimide solution was obtained in the same manner as in Example 1, except that 1.442 g (3.245 mmol) of 6FDA was added instead of BPAF. The obtained polyamideimide solution was purified in the same manner as in Example 1 to obtain a polyamideimide copolymer (PAI-4) with a solid content of 8.3 g. The weight average molecular weight of polystyrene equivalent by GPC was 311,000.
[0113] [Comparative Example 1]
[0114] A polyamideimide solution was obtained in the same manner as in Example 1, except that 0.9547 g (3.245 mmol) of sBPDA was added instead of BPAF. The obtained polyamideimide solution was purified in the same manner as in Example 1 to obtain a polyamideimide copolymer (PAI-5) with a solid content of 8.2 g. The weight-average molecular weight of polystyrene equivalent by GPC was 625,000.
[0115] [Comparative Example 2]
[0116] A polyamideimide solution was obtained in the same manner as in Example 1, except that 1.488 g (3.245 mmol) of BPAF and 0.9547 g (3.245 mmol) of aBPDA were added as tetracarboxylic acid dianhydrides instead of aODPA and BPAF. The obtained polyamideimide solution was purified in the same manner as in Example 1 to obtain a polyamideimide copolymer (PAI-6) with a solid content of 7.5 g. The weight average molecular weight of polystyrene equivalent by GPC was 114,000.
[0117] [Comparative Example 3]
[0118] A polyamideimide solution was obtained in the same manner as in Example 1, except that 1.488 g (3.245 mmol) of BPAF and 1.007 g (3.245 mmol) of sOPDA were added as tetracarboxylic acid dianhydrides instead of aODPA and BPAF. The obtained polyamideimide solution was purified in the same manner as in Example 1 to obtain a polyamideimide copolymer (PAI-7) with a solid content of 7.3 g. The weight average molecular weight of polystyrene by GPC was 100,000.
[0119] [Comparative Example 4]
[0120] A polyamideimide solution was obtained in the same manner as in Example 1, except that 0.9547 g (3.245 mmol) of aBPDA and 1.007 g (3.245 mmol) of sODPA were added as tetracarboxylic acid dianhydrides instead of aODPA and BPAF. The obtained polyamideimide solution was purified in the same manner as in Example 1 to obtain a polyamideimide copolymer (PAI-8) with a solid content of 7.0 g. The weight average molecular weight of polystyrene equivalent by GPC was 97,000.
[0121] [Comparative Example 5]
[0122] A polyamideimide solution was obtained in the same manner as in Example 1, except that 1.007 g (3.245 mmol) of sODPA and 1.441 g (3.245 mmol) of 6FDA were added as tetracarboxylic acid dianhydrides instead of aODPA and BPAF. The obtained polyamideimide solution was purified in the same manner as in Example 1 to obtain a polyamideimide copolymer (PAI-9) with a solid content of 8.4 g. The weight average molecular weight of polystyrene equivalent by GPC was 478,000.
[0123] [Comparative Example 6]
[0124] A polyamideimide solution was obtained in the same manner as in Example 1, except that 1.007 g (3.245 mmol) of 6FDA and 0.9547 g (3.245 mmol) of sBPDA were added as tetracarboxylic acid dianhydrides instead of aODPA and BPAF. The obtained polyamideimide solution was purified in the same manner as in Example 1 to obtain a polyamideimide copolymer (PAI-10) with a solid content of 8.0 g. The weight average molecular weight of polystyrene equivalent by GPC was 179,000.
[0125] [Comparative Example 7]
[0126] A polyamideimide solution was obtained in the same manner as in Example 1, except that 1.007 g (3.245 mmol) of sODPA and 0.9547 g (3.245 mmol) of sBPDA were added as tetracarboxylic acid dianhydrides instead of aODPA and BPAF. The obtained polyamideimide solution was purified in the same manner as in Example 1 to obtain a polyamideimide copolymer (PAI-11) with a solid content of 8.3 g. The weight average molecular weight of polystyrene equivalent by GPC was 593,000.
[0127] [Comparative Example 8]
[0128] A polyamideimide solution was obtained in the same manner as in Example 1, except that 0.9547 g (3.245 mmol) of aBPDA and 0.9547 g (3.245 mmol) of sBPDA were added as tetracarboxylic acid dianhydrides instead of aODPA and BPAF. The obtained polyamideimide solution was purified in the same manner as in Example 1 to obtain a polyamideimide copolymer (PAI-12) with a solid content of 7.9 g. The weight average molecular weight of polystyrene equivalent by GPC was 124,000.
[0129] [Comparative Example 9]
[0130] A polyamideimide solution was obtained in the same manner as in Example 1, except that 0.9547 g (3.245 mmol) of aBPDA and 1.441 g (3.245 mmol) of 6FDA were added as tetracarboxylic acid dianhydrides instead of aODPA and BPAF. The obtained polyamideimide solution was purified in the same manner as in Example 1 to obtain a polyamideimide copolymer (PAI-13) with a solid content of 8.1 g. The weight average molecular weight of polystyrene equivalent by GPC was 77,000.
[0131] [Comparative Example 10]
[0132] A polyamideimide solution was obtained in the same manner as in Example 1, except that 1.488 g (3.245 mmol) of BPAF and 0.9547 g (3.245 mmol) of sBPDA were added as tetracarboxylic acid dianhydrides instead of aODPA and BPAF. The obtained polyamideimide solution was purified in the same manner as in Example 1 to obtain a polyamideimide copolymer (PAI-14) with a solid content of 8.4 g. The weight average molecular weight of polystyrene by GPC was 391,000.
[0133] [Comparative Example 11]
[0134] A polyamideimide solution was obtained in the same manner as in Example 1, except that 1.488 g (3.245 mmol) of BPAF and 1.441 g (3.245 mmol) of 6FDA were added as tetracarboxylic acid dianhydrides instead of aODPA and BPAF. The obtained polyamideimide solution was purified in the same manner as in Example 1 to obtain a polyamideimide copolymer (PAI-15) with a solid content of 7.8 g. The weight average molecular weight of polystyrene equivalent by GPC was 429,000.
[0135] The molar ratios of the components constituting each polyamideimide copolymer obtained as described above are shown in Table 1.
[0136] Film Production
[0137] A resin varnish was prepared by dissolving 5.0 g of each polyamideimide obtained as described above in 45 g of DMAc. Subsequently, the varnish was applied onto a glass plate using a table coater (Gotech AFA-standard), dried in an inert gas oven (Yamato Kagaku INL-45N1) at 70°C for 1 hour, followed by drying at 250°C for 1 hour, and then peeled off from the glass plate to form a film. The film thickness of the obtained film was as shown in Table 1 below.
[0138] Each obtained film was used as an evaluation sample, and the following evaluation was performed.
[0139] <Measurement of Total Light Transmittance and Haze>
[0140] Each film was cut to a size of 30 mm × 30 mm, and the total light transmittance and haze were measured using a haze meter (Nippon Tenshoku Kogyo Co., Ltd., NDH 7000 II) in accordance with ASTM D 1003. Each measured value was standardized to the film thickness (50 µm thickness). The measurement results are as shown in Table 1 below.
[0141] <YI값(옐로우 인덱스) 평가>
[0142] Each film was cut to a size of 30 mm × 30 mm, and in accordance with ASTM E313, the YI value was obtained using a spectrophotometer (Konica Minolta Corporation, CM-5), and the YI value was evaluated according to the following evaluation criteria.
[0143] ○: YI value less than 2
[0144] △: YI value is 2 or greater and less than 3
[0145] ×: YI value is 3 or higher
[0146] The evaluation results were as shown in Table 1 below.
[0147] Character Assessment
[0148] Each film was cut to a predetermined size, and the elastic modulus, fracture stress, and fracture elongation were measured using a small bench tester (manufactured by Shimadzu Seisakusho, Inc., EZ-SX). In addition, the elastic modulus was determined from the slope of the obtained stress-strain curve at stresses between 5 MPa and 10 MPa. Furthermore, the fracture energy was calculated by determining the product of stress and strain (i.e., the area formed by the stress-strain curve) from the stress-strain curve. Based on the fracture energy, toughness was evaluated according to the following evaluation criteria.
[0149] ○: Breaking energy is 0.6J or higher
[0150] △: Breaking energy 0.4J or more and less than 0.6J
[0151] ×: Breaking energy less than 0.4J
[0152] The evaluation results were as shown in Table 1 below.
[0153] Film Wetting
[0154] The contact angle with water on the surface of each film in contact with the glass plate was measured using a contact angle meter (DM300) manufactured by KYOWA INTERFACE SCIENCE. Based on the measured contact angle, the wettability of the film was evaluated according to the following evaluation criteria.
[0155] ○: Water contact angle is 55 degrees or less
[0156] △: Water contact angle greater than 55 degrees and less than or equal to 65 degrees
[0157] ×: Water contact angle exceeds 65 degrees
[0158] The evaluation results were as shown in Table 1 below.
[0159] Film Adhesion
[0160] A decorative coloring agent was applied to the surface of each film in contact with the glass plate such that the film thickness after drying was 2 to 3 μm by screen printing, and a colored coating film was formed by heating and drying at 80°C for 30 minutes to obtain an adhesion evaluation sample. In addition, the decorative coloring agent was prepared as follows.
[0161] (Decorative coloring agent)
[0162] 4.57 g of (2-phenyl-4-aminophenyl)-4-aminobenzoate (PHBAAB), 4.29 g of 4,4'-diamino-3,3'-dicarboxydiphenylmethane (MBAA), 15.61 g of 2,2'-bis[4-(3,4-dicarboxyphenoxy)propanoic acid dianhydride](BPADA), 94.64 g of ethyl benzoate, 0.47 g (6 mmol) of pyridine, and 10 g of toluene were added to a 500 ml separable flask equipped with a nitrogen inlet tube and a stirring device, and the mixture was reacted for 4 hours at 180°C under a nitrogen atmosphere while removing toluene from the system during the process to prepare a polyimide compound solution with a solid content of 20 mass%.
[0163] Next, 12.5g of carbon black and 0.5g of DBP (manufactured by Johoku Kagaku Kogyo Co., Ltd., phosphate ester-based adhesion aid) were mixed with 50g of this solution and dispersed until uniform to produce a decorative coloring material.
[0164] For each sample obtained as described above, the adhesion between the film and the colored coating was evaluated in accordance with JIS K 5600-5-6 (ISO2409). Specifically, a grid-shaped cutting section with 100 squares was cut into the colored coating at 1 mm intervals using a flat edge, and "Cello Tape" (registered trademark) was applied. Afterward, the Cello Tape (registered trademark) was peeled off, and the condition of the colored coating was visually inspected. The evaluation was then performed based on the evaluation criteria of JIS K 5600-5-6 (ISO2409) (a 6-level evaluation from 0 to 5 in order of highest adhesion). The evaluation results are shown in Table 1 below.
[0165]
[0166] As is evident from the evaluation results in Table 1, the polyamideimide copolymer (Examples 1 to 4) using an imide structural unit (Unit I-1) derived from aODPA and a specific imide structural unit (Unit I-2) as tetracarboxylic acid diacid components has excellent optical properties, mechanical properties, wettability, and adhesion compared to the polyamideimide copolymer using an imide structural unit (Unit I-1) and a different imide structural unit (sBPDA) (Comparative Example 1) and the polyamideimide copolymer not having an aODPA-derived structural unit (Comparative Examples 2 to 11).
Claims
Claim 1 A polyamideimide copolymer comprising an imide structural unit and an amide structural unit, wherein the imide structural unit is an imide structural unit I-1 represented by the following formula (1): and at least one imide structural unit I-2 selected from the group consisting of those represented by the following formulas (2) to (5): A amide structural unit A comprising, wherein the amide structural unit is represented by the following formula (6): (However, in equations (1) to (6), X1 to X6 are in the following equation (7): (In the formula, * is a combiner.) expressed as, and in formula (6), Y is, the following formulas (8) to (10): A polyamideimide copolymer characterized by comprising at least one selected from (where * is a linker). Claim 2 In claim 1, a polyamideimide copolymer in which the imide structural unit I-2 is represented by the formula (2). Claim 3 A polyamideimide copolymer according to claim 1, wherein the imide structural unit and the amide structural unit are included in a molar ratio of 2:8 to 8:
2. Claim 4 A film comprising a polyamideimide copolymer as described in any one of claims 1 to 3. Claim 5 In paragraph 4, a film having a water contact angle of 55 degrees or less on the surface of a film with a thickness of 50 μm as measured in accordance with JIS R3257:1999. Claim 6 In paragraph 4, a film used as a cover window of a foldable device. Claim 7 delete Claim 8 delete
Citation Information
Patent Citations
Polyester-amide-imide resin, its precursor and their production
JP1998182822A
Film, resin composition, and production method for polyamide-imide resin
JP2018119141A
Substrate for organic electronic
KR1020150037690A
Poly(amide-imide) copolymer, method of manufacturing the same, poly(amide-imide) copolymer film, window for display device, and display device
US20180237589A1
Soluble polyimide
JP2005272655A
